The Political Economy of Poverty, Vulnerability and Disaster Risk Management : Building Bridges of Resilience, Entrepreneurshi. - Mawere, Munyaradzi (Langaa RPCIG, 2017)
Poverty remains a thorny and topical challenge and research topic to scholars and researchers on African development. Scholars in the Global North have since the Second World War sought to research poverty and underdevelopment in Africa, postulating what they think are the major causes of insipid and abject poverty in the continent, but with little or no success on how to solve the poverty enigma. Sadly, little research and homework have been done by scholars in context (in Africa) on why there seems to be more production rather than eradication of poverty and vulnerability in Africa and among Africans. This book is born out of the realisation for the need for both scholars on the ground and outside Africa to earnestly interrogate and reflect on the poverty situation that continues to haunt the people of Africa and rattle the conscience of the world at large. With contributors from across the continent and beyond, the volume offers a balanced and rigorous, multi-faceted analysis of Africa's poverty and vulnerability from a rich tapestry of perspectives. The volume is handy to scholars and students in the fields of African and development studies, as well as to students of Sociology, Anthropology, Political Science and Policy Studies.
Keywords: Emergency management.; Economic development -- Africa.; Poverty -- Africa.; Africa -- Economic conditions.; Développement économique -- Afrique.; Pauvreté -- Afrique.; Afrique -- Conditions économiques.; POLITICAL SCIENCE -- Public Policy -- Social Security.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Poverty & Homelessness.; Economic development; Economic history; Emergency management; Poverty; Africa